Exploring concept creep: Youth’s portrayal of ADHD on TikTok - Wietske de Vries; Laura Batstra; Arjen van Assen (SSM - Mental Health)
TikTok has quickly become a popular platform for youth to access and share mental health information. Videos discussing characteristics of diagnoses, such as Attention Deficit Hyperactivity Disorder (ADHD), receive significant engagement. However, concerns have been raised about the spread of misinformation and potential self-diagnosis among viewers of these videos.To assess the accuracy of the information shared, we conducted a content analysis of 100 popular TikTok videos. Our findings showed that 55 % of the characteristics that youth attributed to ADHD in their videos did not align with the DSM-5-TR criteria of this diagnosis. Investigation of the top comments further suggests that the majority of the viewers (59,6 %) identified with the depicted behaviors and experiences. Moreover, most of the top-commenters accepted or even validated that these traits were part of ADHD, even though this was often not the case.Our findings illustrate how youth broaden the ADHD concept on TikTok. This bottom-up psychiatrization may affect the self-image of other young people who identify with this content, as they come to understand their own behaviors through a pathological lens. It additionally raises concerns about the already high demand for health care, as individuals may seek help after self-diagnosing. This study highlights the need to make health care providers, educators and parents aware of the misinformation circulating online about ADHD. This would enable them to better support youth and help them to be critical of mental health content they encounter on social media.